Pengaruh Dosis Pupuk NPK dan Jenis Pupuk Pelengkap terhadap Pertumbuhan dan Produksi Cabai (Capsicum annuum L.) - Kus Hendarto; Yohanes Cipta Ginting; Agus Karyanto; Virginia Chintya Amanda (JURNAL AGROTROPIKA, 2021)
This study aims to determine the effect of NPK dosage, types of complementary fertilizers and their interactions on the growth and production of chilies pepper.  This research was conducted in Sukabanjar Village, Gedong Tataan, Pesawaran Regency from July-December 2020.  The experimental design used in this study was a two-factor randomized block design (RBD), namely the dose of NPK fertilizer and the type of complementary fertilizer (4 × 2) with 3 replications.  Each plot consisted of 8 plants so that there were 192 plants.  The first factor was NPK Mutiara fertilizer dose (16:16:16)(N) with N0:0 g/plant, N1:10 g/plant, N2:20 g/plant and N3:30 g/plant.  The second factor is the type of complementary fertilizer (P) with P1 Plant Catalyst and P2 Gandasil D. Homogeneity of variance was tested by Bartlett test, additivity was tested by Tukey test. Then it was continued with analysist of variance and with the Least Significant Difference test (LSD) at the 5% level. Treatment of NPK fertilizer dosage significantly increases growth and yield.  The interaction between the NPK dosage of 20g/plant and type of complementary fertilizers gave highest plant height (95.58 cm). The best  combination was NPK dosage of 20 g/plant and Plant Catalyst fertilizer that gave highest yield (753,17 g/plant equivalent 15.06 ton/ha at population 20,000 plant/ha.Keywords : Chili pepper, complimentary fertilizer, growth, NPK, yield